Sugar amino acids at the anomeric position of carbohydrates: synthesis of spirocyclic amino acids of 6-deoxy-L-lyxofuranose - Bleriot, Y; Simone, M; Wormald, M; Dwek, R; Watkin, D; Fleet, G (2006)
Two anomeric spirodiketopiperazines and one spirohydantoin of 6-deoxy-l-lyxofuranose have been prepared from l-fucono-δ-lactone via ring contraction to the corresponding tetrahydrofuran carboxylate and anomeric functionalization including regioselective bromination and azide displacement. © 2006 Elsevier Ltd. All rights reserved.